The Implementation of the Discovery Learning Model Using a Scientific Approach to Improve the Science Learning Competency of Class VII Students of SMPN 21 Padang - Masnidar, Masnidar; Anhar, Azwir (Literasi Bahasa dan Sastra Jurnal, 2024)
This research aims to improve the learning competence of class VII students at SMPN 21 Padang for the 2017/2018 academic year through the application of the Discovery Learning learning model on the material of the organization of life and the interaction of living things with the environment. This research is Class Action Research (PTK) which was carried out in two cycles. Each cycle consists of planning, implementing actions, observing and reflecting. The research subjects were class VII3 students at SMPN 21 Padang in the 2017/2018 academic year. Data sources are teachers and learners. Data collection techniques through tests and observation sheets. The collected data was then analyzed descriptively qualitatively. Based on the research results, it can be concluded that the application of the Discovery Learning model can improve students' learning competence. The results of the research obtained that the percentage of pre-cycle attitude completeness competency was 79.3%, cycle I was 81.26%, and cycle II was 88.13%. The skills competency of pre-cycle students was 65.20%, cycle I was 72.33%, and cycle II was 74.00%. The knowledge competency of pre-cycle students was 66.43%, cycle I was 75.89%, and cycle II was 83.39%.